Seismic behaviour of composite shear wall with steel reinforced concrete frame and embedded perforated-steel plate - Zhongyi Zhou; Wanlin Cao; Yan Liu; Jianhua Li (Građevinar)
Experiments are conducted on five shear wall specimens of varying design and structural measures in order to investigate seismic behaviour of a composite shear wall with the steel-reinforced concrete frame and an embedded perforated-steel plate. In addition, low-cyclic load is applied on test specimens that have a shear span ratio of 1.5. Using the experimental data, the bearing capacity, stiffness, ductility, hysteretic energy, and failure characteristics of five specimens are analysed. The results show that the composite shear wall (CSW) with the steel reinforced concrete frame (SRCF) and embedded steel plate (ESP) has higher bearing capacity, better ductility, slower degradation of stiffness, and higher energy dissipation capacity, as compared to an ordinary reinforced concrete shear wall. Moreover, its seismic behaviour can be improved by using the ESP of an appropriate thickness. For the ESPs of identical thickness, the results show that the specimen that uses steel ties exhibits better seismic behaviour than those using welding studs. Finally, a computing model that can calculate the bearing capacity of the CSWs is developed. A comparison of calculated and measured results shows that the results are close to each other.